Evaluation of the organizational innovation and self-efficiency levels of health workers - Vasfiye Bayram Değer; Birgül Vural Doğru; Nurgül Arslan (Universidade Estadual de Maringá, 2022)
The aim of this study was determine whether the personal features of the participants create a difference in terms of organizational innovation. This study was conducted with 1234 nurses and midwives. A multiple regression model was created to see and predict the effect on individuals' total innovative scores and self-efficacy scores. The total innovative and the self-efficacy score are predicted with multiple regression analyses. It was observed that the variable that most affected both the total innovative score and the self-efficacy score of the individuals was the education level of the individuals. The fact that midwives and nurses have a certain level of innovative and self-confidence is important for the society to receive better and faster health services. In this study, it was observed that the education level was important for the development of innovative and self-confidence in both groups.